2012
DOI: 10.6061/clinics/2012(07)13
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of Tualang honey on bone structure in experimental postmenopausal rats

Abstract: OBJECTIVE:The objective of this study was to evaluate the effects of Tualang honey on trabecular structure and compare these effects with those of calcium supplementation in ovariectomized rats.METHODS:Forty female, Sprague-Dawley rats were randomly divided into five groups (n = 8): four controls and one test arm. The control arm comprised a baseline control, sham-operated control, ovariectomized control, and ovariectomized calcium-treated rats (receiving 1% calcium in drinking water ad libitum). The test arm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 32 publications
(33 reference statements)
1
39
0
1
Order By: Relevance
“…In addition, Hussain et al [11] reported that honey has similar effects with hormone replacement therapy on bone densitometry in postmenopausal women. Therefore, it was hypothesized that honey may play a role in increasing bone health.Tualang honey is a wild, multi floral honey produced by Apis dorsata bees that form hives on the branches of giant trees named Tualang in the Malaysian rainforest, and it has been reported recently that ovariectomized rats that received Tualang honey showed greater improvements in trabecular bone structure than rats receiving calcium [12], implying the beneficial effects of Tualang honey supplementation on bone. Nevertheless to date, administration of Tualang honey in combination with exercise on bone health and antioxidant status in rats has not been investigated, thus the present study was proposed.…”
mentioning
confidence: 99%
“…In addition, Hussain et al [11] reported that honey has similar effects with hormone replacement therapy on bone densitometry in postmenopausal women. Therefore, it was hypothesized that honey may play a role in increasing bone health.Tualang honey is a wild, multi floral honey produced by Apis dorsata bees that form hives on the branches of giant trees named Tualang in the Malaysian rainforest, and it has been reported recently that ovariectomized rats that received Tualang honey showed greater improvements in trabecular bone structure than rats receiving calcium [12], implying the beneficial effects of Tualang honey supplementation on bone. Nevertheless to date, administration of Tualang honey in combination with exercise on bone health and antioxidant status in rats has not been investigated, thus the present study was proposed.…”
mentioning
confidence: 99%
“…Previous studies showed that tualang honey improved the trabecular structure of bone in OVX rats [4,5] . We used MHCP in this study, and the 5% honey diet tended to decrease (p=0.06) and the 10% honey diet significantly decreased serum CTx concentration in OVX mice without a change in uterine weight.…”
Section: Discussionmentioning
confidence: 89%
“…In addition, honey improved the trabecular structure of bone as assessed using histomorphometry in OVX rats that were orally gavaged daily for 6 weeks [5] . Thus, honey may prevent bone loss due to menopause.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 Oral consumption of honey could improve bone structure in osteoporotic rats. 27,28 In a recent review, it was demonstrated that honey could prevent cancerogenesis through alteration of cell cycle molecular processes 19 and some studies reviewed the effectiveness of honey for wound healing. 18,29,30 Although several studies demonstrated the soft tissue wound healing effect of honey, 18,23,29,30 its effect on bone defects has not been evaluated.…”
Section: 5005/jp-journals-10024-2210mentioning
confidence: 99%